Perubahan Stratifikasi Sosial Masyarakat Pemilik Budidaya Burung Walet di Desa Soga, Kecamatan Marioriwawo, Kabupaten Soppeng - Hisma, Nurul; W. Suhaeb, Firdaus (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This research was conducted to find out (1) the factors causing changes in social stratification of the people who own swiftlet cultivation in Soga Village, Marioriwawo District, Soppeng Regency. (2) The impact of changes in social stratification of the people who own swiftlet cultivation in Soga Village, Marioriwawo District, Soppeng Regency. The results of this study indicate that (1) the factors causing changes in the social stratification of the people who own swiftlet cultivation, namely income factors, social role factors, honor factors and knowledge factors (2) the impact of changes in social stratification of the people who own swiftlet cultivation, namely: changing lifestyles , life and health opportunities for the owner of swiftlet cultivation to receive treatment at the hospital, responses to changes in swiftlet cultivators participating in activities in the village, opportunities for work and business for swiftlet cultivation owners, happiness and socialization in the family, and political behavior of swiftlet cultivators is better than before